(untitled) (Journal of Applied Business and Economics, 2023)
We investigate the relation between the utilization of dual-class shares and the cash flow sensitivity of cash. Dual-class share structures are on the rise and are frequently used as an indicator of governance quality. Almeida, Campello, and Weisbach (2004) measure the cash flow sensitivity of cash as a gauge of savings from current-period cash flow. Our study contributes to both corporate governance and cash management domains by comparing the cash savings practices of dual-class share companies with those of single-class share companies. We discover that dual-class firms exhibit a higher cash flow sensitivity of cash, indicating that they tend to accumulate more cash from their cash flows.